Penerapan Hazard Analysis Critical Control Point (HACCP) terhadap penurunan bahaya mikrobiologis pada makanan khusus anak berbasis hewani di Rumah Sakit Umum Daerah Dr. Soedarsono Pontianak - Widyana Lakshmi Puspita; Yenni Prawiningdyah; Fatma Zuhrotun Nisa (Jurnal Gizi Klinik Indonesia, 2010)
Background: One way to improve the quality of food provision in hospitals is by implementing hazard analysis critical control point (HACCP) in food processing.Objective: The study aimed to identify the effect of HACCP implementation to the decrease of microbiological hazards of foods for children in particular at Nutrition Installation of Dr. Soedarso Hospital of Pontianak.Methods: The study was a quasi experiment that use multiple time series design with intervention and cassation of intervention (ABA time series chain). Samples of the study were animal based food for children, cooking utensils used preparation, processing, and distribution of the food, the food providers and food processing containers. Samples were taken 3 times before and after the implementation of HACCP, each within a week duration.Result: Average germ rate in foods and cooking utensils before implementation of HACCP was relatively high. After the implementation of HACCP there was a decrease. The result of statistical analysis showed that there were effects of HACCP implementation to the reduction of microbiological hazards in foods and cooking utensils (p<0.05). Average score of knowledge on sanitation hygiene of food and practice of sanitation hygiene of foods after HACCP implementation increased. There was an increase of average score of knowledge on food sanitation hygiene and practice of food sanitation hygiene of HACCP implementation (p<0.05). Average score of sanitation hygiene of food processing container after HACCP implementation increased.Conclusion: The implementation of HACCP could reduce microbiological hazards (germ rate) of animal based special foods for children.